2018
DOI: 10.1103/physrevb.97.174417
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the magnetic structure and charge ordering in La1/3Sr2/3FeO3 by neutron powder diffraction and Mössbauer spectroscopy

Abstract: The magnetic ordering of La 1/3 Sr 2/3 FeO 3 perovskite has been studied by neutron powder diffraction and 57 Fe Mössbauer spectroscopy down to 2 K. From symmetry analysis, a chiral helical model and a collinear model are proposed to describe the magnetic structure. Both are commensurate, with propagation vector k = (0,0,1) in R3c space group. In the former model, the magnetic moments of Fe adopt the magnetic space group P 3 2 21 and have helical and antiferromagnetic ordering propagating along the c axis. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…The refined data shows two nonequivalent Fe sites whose ordered magnetic moments are 2.52 and 3.27 μ B , values that are consistent with previous studies [9,37] and are at odd with the ones expected for Fe 5+ and Fe 3+ (3 and 5 μ B ) in a full CD. In the course of this research, a magnetic study on Sr 2/3 La 1/3 FeO 3 has recently been reported [43]. The results of this work are in agreement with our study showing similar conclusions about the possible magnetic groups for a collinear ordering of the Fe moments.…”
Section: B Magnetic Structure Of Sr 2/3 La 1/3 Feosupporting
confidence: 92%
See 2 more Smart Citations
“…The refined data shows two nonequivalent Fe sites whose ordered magnetic moments are 2.52 and 3.27 μ B , values that are consistent with previous studies [9,37] and are at odd with the ones expected for Fe 5+ and Fe 3+ (3 and 5 μ B ) in a full CD. In the course of this research, a magnetic study on Sr 2/3 La 1/3 FeO 3 has recently been reported [43]. The results of this work are in agreement with our study showing similar conclusions about the possible magnetic groups for a collinear ordering of the Fe moments.…”
Section: B Magnetic Structure Of Sr 2/3 La 1/3 Feosupporting
confidence: 92%
“…This CD qualitatively agrees with other techniques such as RXS and BVS but quantitatively is a bit higher maybe due to differences in the temperature dependence for δ 1 and δ 2 . In any case, this technique allows us to discard the occurrence of a full disproportionation in opposite to previous interpretations [19] but in agreement with recent reports [43].…”
Section: Mössbauer Spectra Of Sr 2/3 La 1/3 Feosupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, a neutron diffraction experiment has suggested that the helimagnetic spin structure with q = (1/6, 1/6, 1/6) in the pseudo-cubic cell can be eligible as well as the collinear spin structure. 15 It should be noted here that Ca 2/3 La 1/3 FeO 3 with A-site ordered perovskite structure has recently been found to show two types of spin/charge ordering as a function of temperature. 16,17 Whereas the spin/charge ordering at lower temperatures is the same as that of Sr 2/3 La 1/3 FeO 3 , the other at higher temperatures has charge ordering along [010] and helical spin structure with a propagation vector q = (1/3, 1/3, 1/3) on the pseudo-cubic unit cell.…”
Section: Introductionmentioning
confidence: 71%
“…The ideal structure of perovskite oxides is cubic and typical structural variations from the cubic structure include rotation and tilting of the octahedra, [1] off-centering of the A and/or B cations, [2][3][4] distortion of the octahedra due to the Jahn-Teller effect, [5] and expansion/contraction of the BO 6 octahedral cages. [6] In recent years, perovskite La 1Àx Sr x FeO 3Àδ samples have been extensively investigated due to the fundamental metal-insulator transition [7][8][9][10] and applications of oxygen separation membranes, [11] gas sensors, [12] and cathode materials for solid oxide fuel cells. [13] As a comparison, many studies have been made on perovskite La 1Àx Ba x FeO 3Àδ samples.…”
Section: Introductionmentioning
confidence: 99%